Analysis of Tangential Combustion Instability Modes in a LOX/Kerosene Liquid Rocket Engine Based on OpenFOAM - Guo, Kangkang; Xu, Boqi; Ren, Yongjie; Tong, Yiheng; Nie, Wansheng (Frontiers in Energy Research, 2022)
Self-excited high frequency combustion instability (HFCI) of first-order tangential (1T) mode is captured in a staged-combustion LOX/Kerosene liquid rocket engine based on sprayFOAM solver. The 1T mode combustion instability has two different patterns: standing wave and traveling wave. In the nominal operation condition, the value of oxygen-to-fuel ratio (O/F) is 2.5. All injectors share the same propellant mass flow, and no HFCI occurs. The chamber pressure obtained from the numerical calculation and experiment shows a good agreement, which validate the numerical model. When the fuel mass flow of two injectors on the opposite sides of combustor diameter on the injector face is modified, severe HFCI will occur. The pressure wave node locates at a fixed diameter, showing a 1T standing wave mode. As the O/F increases to 4.4 and the propellant distribution is completely uniform, there is also a HFCI whose wave node shows a spinning behavior, demonstrating a traveling 1T wave mode. Once the HFCI occurs, no matter what standing mode or spinning mode, the heat release from combustion is fed into the resonant acoustic mode. The pressure and heat release oscillate totally in phase temporally and couples spatially. This is the thermoacoustic coupling process that maintaining the HFCI.